Teachers' beliefs about inquiry-based learning and its impact on formative assessment practice. Issue 3 (2nd July 2020) - Correia, Catarina F.; Harrison, Chris
ABSTRACT: Background: Inquiry pedagogy has been advocated as means to engage and motivate students to learn science. The development of teacher formative assessment practice in inquiry is key for a successful implementation of student-centred inquiry pedagogy in the classroom. Purpose: This study explores secondary science teachers' espoused beliefs about inquiry-based learning and the impact this has on their actual formative assessment practice in the classroom. Sample: The study involved two experienced science teachers. Design and methods: This study provides two case studies of developing practice as teachers attempt to move towards student-centred inquiry approaches. The study combines teacher semi-structured interviews, recordings of teacher–student(s) conversations in inquiry lessons, and field notes of classroom observations. Following a qualitative approach, we did a thematic analysis of teacher interviews to infer teachers' espoused beliefs about inquiry-based learning and about their perceptions of their role as teachers in inquiry lessons. We used a combination of the ESRU model and the Convergent/Divergent assessment framework to characterise teachers' formative assessment conversations with their students in inquiry lessons. Results: Our findings show that teachers' beliefs about inquiry are consistent with how they teach and assess inquiry, and that the promotion of student autonomy is influenced by teacher beliefs. Teachers who position themselves as facilitators adopt more open guided inquiry approaches, while teachers who position themselves as 'shepherds' adopt more directed approaches to inquiry. This has important implications for students' autonomy and self-regulation in inquiry lessons.